Structure of the DNA-SspC Complex: Implications for DNA Packaging, Protection, and Repair in Bacterial Spores - Frenkiel-Krispin, Daphna (American Society for Microbiology, 2004)
Bacterial spores have long been recognized as the sturdiest known life forms on earth, revealing extraordinary resistance to a broad range of environmental assaults. A family of highly conserved spore-specific DNA-binding proteins, termed α/β-type small, acid-soluble spore proteins (SASP), plays a major role in mediating spore resistance. The mechanism by which these proteins exert their protective activity remains poorly understood, in part due to the lack of structural data on the DNA-SASP complex. By using cryoelectron microscopy, we have determined the structure of the helical complex formed between DNA and SspC, a characteristic member of the α/β-type SASP family. The protein is found to fully coat the DNA, forming distinct protruding domains, and to modify DNA structure such that it adopts a 3.2-nm pitch. The protruding SspC motifs allow for interdigitation of adjacent DNA-SspC filaments into a tightly packed assembly of nucleoprotein helices. By effectively sequestering DNA molecules, this dense assembly of filaments is proposed to enhance and complement DNA protection obtained by DNA saturation with the α/β-type SASP.